A study of the swine flu (H1N1) epidemic among health care providers of a medical college hospital of Delhi - Om Prakash Rajoura; Rupali Roy; Paras Agarwal; Anjur Tupil Kannan (Wolters Kluwer Medknow Publications, 2011)
Background: Influenza viruses cause annual epidemics and occasional pandemics that have claimed the lives of millions. Understanding the role of specific perceptions in motivating people to engage in precautionary behavior may help health communicators to improve their messages about outbreaks of new infectious disease generally and swine flu specifically. Objectives: To study the knowledge and practices of health care providers regarding swine flu and to study the attitudes and practices of health care providers toward the prevention of the swine flu epidemic. Materials and Methods: The present study was a cross-sectional (descriptive) study and was conducted in the month of September, 2009, among doctors and nurses. A maximum of 40% of the total health care providers of GTB Hospital were covered because of feasibility and logistics, and, therefore, the sample size was 334. Results: Around 75% of the health care providers were aware about the symptoms of swine flu. Mostly, all study subjects were aware that it is transmitted through droplet infection. Correct knowledge of the incubation period of swine flu was known to 80% of the doctors and 69% of the nurses. Knowledge about high-risk groups (contacts, travelers, health care providers) was observed among 88% of the doctors and 78.8% of the nurses. Practice of wearing mask during duty hours was observed among 82.6% of doctors and 85% of nurses, whereas of the total study population, only 40% were correctly using mask during duty hours. Conclusions: Significant gaps observed between knowledge and actual practice of the Health Care Provider regarding swine flu need to be filled by appropriate training. Data indicate that the health care providers are very intellectual, but they do not themselves practice what they preach.